Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 10 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Cypseloides storeri Navarro, Peterson, Escalante & Benitez, 1992" ] } The dataset includes 10 records from 4 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002380-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences